The 3D lightweight structural characteristics of the beetle forewing: Verification. (October 2021) - Chen, Jinxiang; Huang, Jiaying; Pan, Longcheng; Zhao, Tidong; Zhang, Xiaoming; Lin, Haiwei
Abstract: To practically and effectively develop lightweight and high-strength biomimetic materials based on the beetle forewing, the mechanical properties and failure mechanism of the pure-trabecular beetle elytron plate (TBEP) model and the "false biomimetic proposition" horizontal tube (HT) model mentioned in a previous paper were investigated through compression experiments in this paper. The results show that: the TBEP model has excellent compression performance and the strength/mass ratio of the HT model is even less than that of the honeycomb plate. This is because the existing horizontal tubes in the HT model have applied lateral force to the trabeculae, causing the horizontal tubes and trabeculae to form cracks at their contact due to their mutual pressing. Meanwhile, the horizontal tubes do not help prevent the deformation of the trabecula in the TBEP model, including bulging or shrinkage at the ends. This study provides an experimental and theoretical basis for the reader to identify the series of "false biomimetic propositions" appearing in the field of beetle forewing biomimetic structures; additionally, it will play an active role in preventing the abuse of bionics concepts and purifying the academic environment. It also provides direct guidance for the future development of durable, high compression resistance, lightweight and high-strength materials.